Study of Land Use Change Map in the Irrigation Areas of Gebong and Sesaot, West Lombok Regency - Suripto; Jupri; Sugiarta, Lalu Ade; Anggraeni, Juraedah Dwi (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The conversion of an area's land cover can provide social and economic benefits for the area but also often has important impacts on the environment. Thus, knowledge and skills in reading land cover change maps from satellite images are very important for Environmental Science students. Work practice for students of the Mataram University Environmental Studies Program was carried out at the West Lombok PUPR Service with the aim of increasing knowledge and skills about reading, analyzing and interpreting land cover change maps through geographic information systems, especially for the irrigation areas of Gebong and Sesaot, West Lombok. Work practice was carried out using lecture, simulations, and practice with assistance methods The results show that participant was proficient in reading, analyzing and interpreting land cover change maps using both the maxilum likelihood method and the manual digitization method. From the results of work practices using the maximum likelihood and manual digitization method, it was known that in the Gebong irrigation area from 2018 to 2023 there will be a reduction in the area of ​​3% (3%) of paddy fields, 1% (4%) of vegetated land, and an increase of 3 (8%) of built-up land. In the Sesaot irrigation area, there was a reduction in the area of ​​vegetated land by 10% (6%), an increase in the area of ​​rice fields by 8% (3%), and built-up land by 2% (2%). It had been confirmed that the built-up land in the two irrigation areas consists of residential and industrial lands.